Is the Initial Treatment in Stage IB2 Cervical Carcinoma Neoadjuvant Chemothreapy or Primary Surgery? - Turan, Taner; Akdağ, Derya; Boran, Nurettin; Yüksel, Nuray; Tulunay, Gökhan; Özgül, Nejat; Köse, Faruk (Gynecology Obstetrics & Reproductive Medicine, 2009)
OBJECTIVE: It is expected that neoadjuvant chemotherapy (NACT) decrease tumor size, increase the operability and improve surgical-pathologic risk factors so that improve the survival. In this study we evaluated the effect of NACT on surgical-pathologic risk factors and survival. STUDY DESIGN: Between 1993 and 2007, the data of patients with stage IB2 cervical cancer were reviewed. Twenty-four patients who were treated with NACT followed by radical surgery (RS) were compared with 15 patients underwent primary RS. After two or three courses of chemotherapy patients were reassessed and RS was performed to patients whose tumor size was less than 40mm. In both groups all patients underwent type III radical hysterectomy + bilateral salpingo-oophorectomy + systematic paraaortic and bilateral pelvic lymphadenectomy. RESULTS: The mean size of the tumor mass was 50.1mm. Nine patients were acccepted as responder (complete clinical response + partial clinical response) and 15 patients as unresponder (stabile disease) after NACT. The surgical-pathologic risk factors didn’t improve with NACT except for stromal invasion. The median follow-up was 48 months. Overall survival and disease free survival was 86.7% in RS group, this ratio was 80% in NACT unresponder group and 66.7% in NACT responder group (p=0.501). CONCLUSION: NACT didn’t improve either the surgical-pathologic risk factors expect for stromal invasion or survival in patients with stage IB2 cervical carcinoma. It appears that we have disappointment with this treatment modality.